Spin wave modes in a cylindrical nanowire in crossover dipolar-exchange regime. (18th December 2018) - Rychły, J; Tkachenko, V S; Kłos, J W; Kuchko, A; Krawczyk, M
Abstract: Nanoscale magnetic systems have been studied extensively in various geometries, such as wires of different cross-sections, arrays of wires, dots, rings, etc. Such systems have interesting physical properties and promising applications in advanced magnetic devices. Uniform magnetic nanowires are the basic structures which were broadly investigated. However, some of their dynamical properties, like: (anti)crossing between the spin wave modes and impact of the magnetic field on the spin wave spectrum, still need to be exploited. We continue this research by investigation of the spin wave dynamics in solid Ni nanowire of the circular cross-section. We use two approaches: semi-analytical calculations and numerical computations based on the finite element method. We solve coupled Landau–Lifshitz and Maxwell equations and consider both dipolar and exchange interactions. We identify the dispersion brunches and their (anti)crossing by plotting the spatial profiles of spin wave amplitudes and magnetostatic potential. We also check how we can tune the spectrum of the modes by application of the external magnetic field and how it affects the modes and their dominating type of interaction.